EFFECIENCY OF IMMOBILIZED POLYPHENOL OXIDASE ON SOME TEXTILE DYES DEGRADATION USING BATCH OPERATION SYSTEM BY PACKED BED BIOREACTOR - Hussein, S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
In the current study, three types of common plants, namely Tomato (Solanum lycopersicum), Cucumber (Cucumis sativus) and Orange (Citrus sinensis) were obtained and screened for their polyphenol oxidase (PPO) activity, Among the three plants, Solanum lycopersicum was chosen with maximum enzymatic activity, it had the highest productivity of the enzyme (23733 U/mg protein).The PPO from Solanum lycopersicum was purified using two steps: concentration by sucrose and gel filtration by using Sephacryl S-200. The results showed an increase in the final purification folds by 2.4 times with an enzyme yield of 32.6%. The immobilization studies showed that PPO was more stable when immobilized on chitosan by covalent linkage with immobilization ratio of 62%, in comparison with agar-agar by entrapment method (36%). The removal efficiency of crude and partial purified PPO was studied with textile dyes, including yellow, red, black and blue dyes at optimum conditions: pH 5, temperature 40oC after 3 hrs. Maximum removal efficiency of dyes observed with crude PPO were 53.9, 81.4, 86.5 and 79.6% respectively. However, purified PPO displayed removal efficiency reached 60.3, 84.3, 84.6 and 77.5% respectively. The potential of immobilized PPO on chitosan was evaluated by decolorization of black textile dye in packed bed bioreactor in batch operation. The results indicated that immobilized PPO in batch operation has the ability to remove 99% of the dye after 2 hrs, and the results showed a positive relationship between the degradation rate and incubation time in batch operation.